Assessing performance and stability of yellow rust resistance, heat tolerance, and agronomic performance in diverse bread wheat genotypes for enhancing resilience to climate change under Egyptian conditions - Megahed, Eman M. A.; Awaad, Hassan A.; Ramadan, Ismail E.; Abdul-Hamid, Mohamed I. E.; Sweelam, Abdallah A.; El-Naggar, Doaa R.; Mansour, Elsayed (Frontiers in Plant Science, 2022)
Yellow rust and heat stress adversatively impact the growth and production of bread wheat in particular under rising adverse environmental conditions. The stability of grain yield is a pivotal purpose of plant breeders to improve wheat production and ensure global food security in particular under abrupt climate change. The obtained results displayed significant differences among the tested locations, sowing dates, and genotypes for most measured traits. The yellow rust measurements evaluated under the field conditions including final rust severity (FRS), the average coefficient of infection (ACI), and area under the disease progress curve (AUDPC) revealed that Giza-171, Misr-1, Gemmiza-12, Shandweel-1, Sids-13, Line-1, Line-2, and Line-55 had better resistance. Based on heat sensitivity measurements, Line-1 and Line-2 followed by Line-35, Shandweel-1 and Line-55 were classified as more tolerant to heat stress than the remaining genotypes. The genotypes Line-55, Gemmeiza-12, Giza-171, Line-1, Line-2, and Misr-1 were able to maintain acceptable agronomic performance under timely and late sowing dates in all evaluated environments. Indeed, Line-1, Line-2, and Line-55 produced the highest yield traits under late sowing dates in all environments. Different statistical procedures were employed to explore the stability and adaptability of tested genotypes i.e., joint regression, stratified ranking, Wricke's Ecovalence values, cultivar superiority, additive main effects, and multiplicative interaction (AMMI), AMMI stability value, and genotype plus genotype-by-environment interaction (GGE). The applied stability parameters were similar for describing the stability of the evaluated wheat genotypes. The results indicated that Gemmeiza-12, Giza-171, Sids-12, Sids-13, Misr-1 Shandweel-1, Line-1, Line-2, and Line-55 were desirable and stable. The heatmap and hierarchical clustering were exploited for dividing the evaluated bread wheat genotypes into different clusters based on yellow rust resistance measurements, heat tolerance indices, and agronomic performance. Line-1 and Line-2 had the best performance for all rust resistance, heat tolerance, and agronomic performance followed by Giza-171, Line-55, Line-35, Gemmeiza-12, Shandweel-1, Misr-1, and Sids-13. The obtained results provide evidence of utilizing promising genotypes in rust resistance, heat tolerance, and agronomic performance in breeding programs for improving wheat grain yield stability mainly under climate change.